Conditions for collapse: Chronic nutrient enrichment increases native insect density linked to salt marsh dieback. (February 2023) - Tomasula, Jewel; Maguire, Billie; Rippel, Tyler M.; Lopez, Eddie; Perez, Stephanie; Arab, Ali; Murphy, Shannon M.; Wimp, Gina M.
Abstract: Ecosystems are enduring new intensities and temporal patterns of stressors, yet little is understood about the conditions that result in ecological collapse. We examined how different conditions of nutrient enrichment affect densities of a native insect that feeds upon a salt marsh foundation plant species, with subsequent effects on salt marsh dieback. Dieback is the abrupt death of salt marsh vegetation, leaving barren mudflats. In a natural salt marsh, we set up a full factorial experiment in which we crossed the amount (low, medium, high) with duration (one-year pulse or a two-year press) of nutrient addition. We recorded stem-borer density, plant tissue percent nitrogen, and percent dieback within each plot. We found the most dieback occurred in the high press plots (median of 25 % dieback and maximum of 80 % dieback). When we compared the effects of nutrient amount and duration on dieback, we found an effect of nutrient amount and a marginal effect of nutrient duration. We found that densities of stem-borer larvae were nearly four times greater in high press plots (20 % of stems) than in control plots (5.6 % of stems). By comparing linked and independent Bayesian hierarchical models, we determined both plant percent nitrogen and stem-borer densities contributed to salt marsh dieback. Our findings link nutrient enrichment with an increase in larval herbivory as a cause of salt marsh dieback. Broadly, we provide evidence that chronically high nutrient enrichment has a synergistic effect with a biotic agent and is a condition leading to ecosystem collapse.